A Study Of Feminist Ehical Dimensions In Jai Nimbkar’s Come Rain - Bamane, Sujata (Advances in Social Sciences Research Journal, 2017)
Ethical discourse is a manifestation of masculine perspective. However, woman-centric approach to ethics is known as Feminist Ethics. It addresses to the subservient position of woman against man’s dominating one. The present paper offers a study of Ann, a female protagonist in Jai Nimbkar’s novel, Come Rain (1993). It aims at studying a character of Ann projected as an ‘idealistic and rather unconventional American girl’ exploring an inner and outer space in her ‘stormy relationship with her Indian husband and his family’. The novel focuses on the patterns of male-domination and woman’s struggle for her liberation from the rigid norms of Indian society. It too is an investigation of whether moral reasoning based on the feminist Care and justice ethics can offer solace to Ann’s logical state of mind? Can she by the end of the novel exist as an independent individual entity? To what extent does Jai Nimbkar keep her story engaged with feminist ethical concerns to offer equal rights to woman and achieve a balanced picture of society? and so on.